Comparison of osteogenic differentiation potential of induced pluripotent stem cells and buccal fat pad stem cells on 3D-printed HA/[beta]-TCP collagen-coated scaffolds - Hashemi, Sheida; Mohammadi Amirabad, Leila; Farzad-Mohajeri, Saeed; Rezai Rad, Maryam; Fahimipour, Farahnaz; Ardeshirylajimi, Abdolreza; Dashtimoghadam, Erfan (Cell and tissue research, 2021)
Production of a 3D bone construct with high-yield differentiated cells using an appropriate cell source provides a reliable strategy for different purposes such as therapeutic screening of the drugs. Although adult stem cells can be a good source, their application is limited due to invasive procedure of their isolation and low yield of differentiation. Patient-specific human-induced pluripotent stem cells (hiPSCs) can be an alternative due to their long-term self-renewal capacity and pluripotency after several passages, resolving the requirement of a large number of progenitor cells. In this study, a new biphasic 3D-printed collagen-coated HA/[beta]-TCP scaffold was fabricated to provide a 3D environment for the cells. The fabricated scaffolds were characterized by the 3D laser scanning digital microscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and mechanical test. Then, the osteogenesis potential of the hiPSC-seeded scaffolds was investigated compared to the buccal fat pad stem cell (BFPSC)-seeded scaffolds through in vitro and in vivo studies. In vitro results demonstrated up-regulated expressions of osteogenesis-related genes of RUNX2, ALP, BMP2, and COL1 compared to the BFPSC-seeded scaffolds. In vivo results on calvarial defects in the rats confirmed a higher bone formation in the hiPSC-seeded scaffolds compared to the BFPSC-seeded groups. The immunofluorescence assay also showed higher expression levels of collagen I and osteocalcin proteins in the hiPSC-seeded scaffolds. It can be concluded that using the hiPSC-seeded scaffolds can lead to a high yield of osteogenesis, and the hiPSCs can be used as a superior stem cell source compared to BFPSCs for bone-like construct bioengineering.